2011
DOI: 10.4103/0259-1162.94783
|View full text |Cite
|
Sign up to set email alerts
|

A very common case become rare: Anesthetic considerations of lepromatous leprosy

Abstract: Leprosy or Hansen's disease is very uncommon in developed countries. More than 80% of the world's cases occurs and still reported from developing countries. But nowadays due to increase in international affairs, medical tourism, globalization and immigration, there is increasing possibility to find patients anywhere, which require anesthesia for surgical interventions. Leprosy is a chronic infectious disease caused by Mycobacterium leprae and involves mainly skin, peripheral nervous system, upper respiratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Clofazimine-induced significant side effects are changes in skin color, rashes, itching, elevated blood sugar, retinopathy, nephrotoxicity, eosinophilic enteropathy, and cardiac arrhythmia [10]. Dapsone, a folate antagonist, has significant adverse effects, including hemolytic anemia, methemoglobinemia, agranulocytosis, abnormalities in liver function tests, jaundice, toxic or cholestatic hepatitis, peripheral neuropathy with primary motor function loss, psychosis, headache, dizziness, nausea, vomiting, dapsone hypersensitivity syndrome (DHS) [5,11]. DHS is a rare but life-threatening side effect of the drug characterized by fever, skin rash, leukemoid reaction, eosinophilia, thrombocytosis, lymphadenopathy, hepatic, pulmonary, and other systemic manifestations and requires immediate action [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clofazimine-induced significant side effects are changes in skin color, rashes, itching, elevated blood sugar, retinopathy, nephrotoxicity, eosinophilic enteropathy, and cardiac arrhythmia [10]. Dapsone, a folate antagonist, has significant adverse effects, including hemolytic anemia, methemoglobinemia, agranulocytosis, abnormalities in liver function tests, jaundice, toxic or cholestatic hepatitis, peripheral neuropathy with primary motor function loss, psychosis, headache, dizziness, nausea, vomiting, dapsone hypersensitivity syndrome (DHS) [5,11]. DHS is a rare but life-threatening side effect of the drug characterized by fever, skin rash, leukemoid reaction, eosinophilia, thrombocytosis, lymphadenopathy, hepatic, pulmonary, and other systemic manifestations and requires immediate action [12].…”
Section: Discussionmentioning
confidence: 99%
“…While leprosy and lepra reaction cases are frequently encountered by dermatologists, as anesthesiologists, encountering these patients for some planned surgical procedure is rare and relatively scarce in the literature today [ 5 ]. Nevertheless, evidence of the perioperative lepra reaction and its prevention strategy is either absent or hardly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in drug metabolism and clearance as a result of hepatorenal dysfunction in leprosy causes prolongation of awaking period after anesthesia. 3 Drugs used for leprosy (Dapson, Rifampisin, Klofazimin) have multiple side effects that affect many systems. Dapson may cause hemolytic anemia, methemoglobinemia, agranulositosis, hepatitis, peripheral neuropathy, psychosis and leprosy reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Sahu et al reported a successful general anesthesia administration to a leprosy patient with renal cell carcinoma. 3 There are also successful regional anesthesia methods in the literature. 15 Careful preoperative evaluation, sufficient perioperative preparation, close follow up and monitorization are important steps of anesthesia induction in leprosy patients with respiratory and cardiac dysautonomia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation